Strengthening Health Systems Using Innovative Digital Health Technologies in Africa - Ibeneme, Sunny; Karamagi, Humphrey; Muneene, Derrick; Goswami, Kajali; Chisaka, Noel; Okeibunor, Joseph (Frontiers in Digital Health, 2022)
While effective health systems are needed to advance Universal Health Coverage and actualize the health Sustainable Development Goals, information system verticalization remains a challenge among African health systems. Most investments are vertical, partner-driven and program-specific with limited system-wide impacts. Poor linkages exist amongst different solutions as they are not designed to capture robust data across multiple programmatic areas. To address these challenges, the World Health Organization Africa Regional Office has proposed the adoption of a Digital Health Platform (DHP) to streamline different solutions to a cohesive whole. The DHP presents a pragmatic approach of bringing multiple platforms together using recognized standards to create a national infostructure, which bridges information solutions toward healthy and sustainable outcomes. It has capacities to curate accurate, high fidelity and timely data feedback loops needed to strengthen and continuously improve program delivery, monitoring, management, and informed decision-making at every level of the health system regardless of location. This paper contributes to the ongoing regional conversations on the need to harness innovative digital solutions to improve healthcare delivery in Africa.